Intellectual Capital, Foreign and Female Executives in the Profitability of Indonesia’s Banks - Saarce Elsye Hatane; Felicia Prayogo Wibowo; Hendri Kwistianus; Hatane Semuel (International Journal of Organizational Behavior and Policy, 2024)
In order to produce profits for Indonesian banking firms, this study is to investigate the qualities of the board of directors as leaders in business management and their capacity to handle intellectual capital. The observation period was in 2016-2020. The observed characteristic of the board of directors is the role of foreign directors and female directors. The results of the study show that foreign directors reduce Return on Assets. It seems that the domestic boards of banking companies in Indonesia have a better understanding and control of market conditions in Indonesia so that they are able to increase bank profitability. Similarly, female directors who excel at managing asset banks in Indonesia. Managerial banks in Indonesia, on the other hand, are able to manage their intellectual capital to maximize profits, both through asset and equity management. This study contributes to the validation of the upper-echelon theory, which demonstrates the function of top management teams in firm management.